Platform An E-Commerce Platform for Coffee MSMEs: System Design and Basic Features - Emilia Hesti; Afifah Syifah Kaila; Ade Silvia Handayani; Leni Novianti; M Arief Rakhman (Komunitas Dosen Indonesia, 2025)
Digitalization of Micro, Small, and Medium Enterprises (MSMEs) has emerged as a strategic necessity in the era of digital transformation. However, many coffee-based MSMEs in Indonesia continue to rely on third-party marketplace platforms that limit autonomy over customer data, pricing control, and brand personalization. This study aims to address these constraints by designing and developing an independent, web-based e-commerce system that aligns with the specific operational needs of coffee MSMEs particularly those seeking low-cost, user-friendly solutions that enable direct customer engagement and reduce commission-based dependencies. The system was developed using Laravel for the backend and Vite.js for the frontend, adhering to the sequential stages of the waterfall model: requirements analysis, system design, implementation, and testing. Key features include product catalog management, shopping cart functionality, manual payment upload, and product review integration. Black-box testing confirmed that all features operated without critical errors under typical usage conditions. Usability testing conducted with five MSME users resulted in an average satisfaction score of 4.23 out of 5 (83%), with high ratings for ease of navigation and interface responsiveness. Performance metrics, including average page load time (<=3 seconds), device compatibility, and user flow scalability, met expected standards. Although the current system employs manual payment validation, future enhancements will focus on integrating secure payment gateways, real-time analytics dashboards, and modular APIs. In summary, the platform offers a practical and scalable e-commerce solution tailored to the autonomy and contextual demands of Indonesia's coffee MSMEs.